1986
DOI: 10.1007/bf02556714
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid glands, calcium, and vitamin D in experimental fluorosis in pigs

Abstract: The purpose of this study was to determine whether total serum calcium, parathyroid gland structure, and/or levels of parathyroid hormone, 1,25 and 24,25 DHCC, are altered in pigs with dental and skeletal fluorosis. Eight experimental animals receiving 2 mg F-/kg b.w. per day from age 8-14 months were compared with eight controls. Concentrations of plasma fluoride and total plasma calcium were assessed at intervals throughout the experiment and during a 48 hour period at day 110-111 of the experiment. At the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
4
13
0
Order By: Relevance
“…Serum vitamin D levels in ruminants with fluorosis were measured for the first time in this study according to our knowledge of the literature, and they were not changed significantly according to our findings. These findings are consistent with the findings of an experimental study in pigs (15). In the present study, adequate levels of vitamin D were determined, which facilitates absorption of Ca from the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Serum vitamin D levels in ruminants with fluorosis were measured for the first time in this study according to our knowledge of the literature, and they were not changed significantly according to our findings. These findings are consistent with the findings of an experimental study in pigs (15). In the present study, adequate levels of vitamin D were determined, which facilitates absorption of Ca from the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, adequate levels of vitamin D were determined, which facilitates absorption of Ca from the gastrointestinal tract. Similar findings were reported in experimental studies by other researchers (14,15). However, the same researchers reported that disturbance of Ca homeostasis is not a necessary finding in dental and skeletal fluorosis and consequently vitamin D does not prevent the deleterious effects of F on motor coordination and teeth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A level of 175 ppm F in drinking water is lethal for about one-third of the rats within 10 days when started at weaning; the remaining rats have stunted growth (Mullenix et al, 1995). No changes in plasma calcium were found in adult rats fed food pellets containing 450 mg F/kg for 8 wks (Appleton, 1994) or pigs receiving a daily oral dose of 2 mg F/kg body weight for 6 mos (Andersen et al, 1986). In the pigs, no changes in immunoreactive PTH and 1,25 vitamin D or 24,25 vitamin D metabolites could be found (Andersen et al, 1986).…”
Section: The Rat As a Model For Enamel Fluorosismentioning
confidence: 99%
“…No changes in plasma calcium were found in adult rats fed food pellets containing 450 mg F/kg for 8 wks (Appleton, 1994) or pigs receiving a daily oral dose of 2 mg F/kg body weight for 6 mos (Andersen et al, 1986). In the pigs, no changes in immunoreactive PTH and 1,25 vitamin D or 24,25 vitamin D metabolites could be found (Andersen et al, 1986). This indicates that, at those doses, fluoride does not interfere with calcium homeostasis.…”
Section: The Rat As a Model For Enamel Fluorosismentioning
confidence: 99%